PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sukardin Sukardin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
Effect of Financial Performance Share Price in the Banking Companies listed on the Indonesia Stock Exchange Year 2013-2015. This study aimed to determine the effect the Current Ratio, Debt to Equity Ratio, Return on Equity, and Working Capital Turnover partially, or simultaneously to the Company's stock price on the Banking Companies listed on the Indonesia Stock Exchange Year 2013-2015. The population in this study is the Banking Companies listed on the Indonesian stock exchange by 42 companies. Samples were ten (10) companies were selected based on the criteria: Banking Companies listed on the Indonesia Stock Exchange Year 2013 to 2015; Publishes audited financial statements; Having the advantage (profit); and never share Cash dividends during the observation period. The results of this study indicate that the Current Ratio (X1) Debt to Equity Ratio (X2) and Working Capital Turnover (X4) partially no significant effect. While Return On Equity (X3) positive and significant impact on stock prices in the Banking Companies listed on the Indonesia Stock Exchange Year 2013-2015. Simultaneous Current Ratio (X1), Debt to Equity Ratio (X2), Return on Equity (X3), and the Working Capital Turnover (X4) Positive and significant effect on stock price on Banking Companies listed on the Indonesia Stock Exchange Year 2013-2015 , The dominant influential variable is Return On Equity (X3).